Statistics in Early Childhood and Primary Education Supporting Early Statistical and Probabilistic Thinking (Early Mathematics Learning and Development,, 2018)
This compilation focuses on the theory and conceptualisation of statistics and probability in the early years and the development of young children's (ages 3-10) understanding of data and chance. It provides a comprehensive overview of cutting-edge international research on the development of young learners' reasoning about data and chance in formal, informal, and non-formal educational contexts. The authors share insights into young children's statistical and probabilistic reasoning and provide early childhood educators and researchers with a wealth of illustrative examples, suggestions, and practical strategies on how to address the challenges arising from the introduction of statistical and probabilistic concepts in pre-school and school curricula. This collection will inform practices in research and teaching by providing a detailed account of current best practices, challenges, and issues, and of future trends and directions in early statistical and probabilistic learning worldwide. Further, it will contribute to future research and theory building by addressing theoretical, epistemological, and methodological considerations regarding the design of probability and statistics learning environments for young children.